Overlap of Multiple Sclerosis and Antiphospholipid Syndrome - İbrahim Tekeoğlu,; Temel Tombul,; Özcan Hız,; Elif Gülcü,; Murat Toprak, (Archives of Rheumatology, 2009)
Antiphospholipid syndrome (APS) and multiple sclerosis (MS) are two diseases that may show similar clinical and radiological findings and sometimes cause confusion. In the presence of thrombosis, repetitious abortion history, and lupus anticoagulant antibodies or anticardiolipin antibodies, APS should be considered. However, in previous studies, autoantibody levels were detected as being high in MS patients when compared to the normal population. Laboratory study of a patient with fever, fatigue, joint pain and cyanosis in the ankles since 1995 and history of two abortions at 6 weeks gestation revealed: C-reactive protein: (++++), erythrocyte sedimentation rate: 70 mm/hour, antinuclear antibodies: 1/1000 homogeneous, and LE cell positivity. Brain magnetic resonance imaging, visual evoked potantial, somatosensorial evoked potential, and oligoclonal band investigations of the patient, who applied to the Neurology Clinic of the hospital in 1999 with complaints of disruption in walking, imbalance and fatigue, were found compatible with MS. The patient had suffered from recurrent attacks and had been directed to our clinic with probable diagnosis of systemic lupus erythematosus when pain in knees and macular style skin lesion on the right ankle finally developed in 2007. Investigations conducted at six-month time intervals revealed anticardiolipin IgG: positive, anticardiolipin IgM: negative and antinuclear antibody (ANA): positive. When ANA and anticardiolipin IgG positivity and abortion history of the patient were evaluated together, APS accompanying MS was diagnosed and 100 mg aspirin was added to the treatment. In conclusion, MS and APS can not only appear together but may also imitate each other. Thus, cases diagnosed as MS should be carefully evaluated in terms of clinical and laboratory findings of APS. (Turk J Rheumatol 2009; 24: 106-9)